Fluorescence Enhancement of Dicyanomethylene-4H-Pyran Derivatives in Solid State for Visualization of Latent Fingerprints - Cai, Yi; Hou, Ting-Ting; Wang, Cai-Yun; Tang, Ying-Hao; Zhang, Zhen-Yu; Zhang, Deteng; Zhu, Ming-Qiang; Wang, Ya-Long (Frontiers in Chemistry, 2022)
The efficient development of latent fingerprint (LFP) is attractively important for criminal investigation. The low-cost and high-contrast developer is still a challenge. In this study, we designed and synthesized dicyanomethylene-4H-pyran (DCM) derivatives PZ-DCM and Boc-PZ-DCM by introducing of large steric hindrance group Boc, the solid-state fluorescence of DCM derivatives was greatly enhanced. The low-cost fluorescent LFP developers were prepared by blending with different proportion of montmorillonite (MMT). As a result, clear and high contrast fingerprint patterns were obtained with dusting method by the developer with 3% content of Boc-PZ-DCM. Furthermore, we employed the developer with 3% content of Boc-PZ-DCM to develop the sweat latent fingerprints on different substrates by powder dusting, and collected clear fingerprint patterns, indicating that the developer is universal. In a word, the Boc-PZ-DCM/MMT powder is a promising candidate for LFP developer.